A rigorous matrix procedure for calculating the line constants and wave parameters of uniform MTLs using SMT/PMU. (2nd June 2017) - Brandão Faria, José A.; Araneo, Rodolfo
Summary: Real‐time monitoring of the operation state of wide‐area transmission line links has become possible with the help of phasor meter units. Synchronized information acquired by phasor meter units needs to be adequately processed to permit the accurate estimation of the line constants of the transmission link. In this paper, a novel general rigorous compact procedure for correctly processing the measured voltage and current phasors of uniform multiconductor transmission line systems is proposed. The procedure based on the ABCD matrix and on modal analysis techniques applies to transposed or untransposed multiconductor transmission lines, with arbitrary geometry, number of conductors, and length. The proposed algorithm, adequate for multiport structures, avoids the approximations usually required by ordinary methods mostly focused on lumped parameters and on 2‐port approaches. The proposed matrix procedure is illustrated and validated using simulation results.